The relationship between observable self-talk and competitive junior tennis players' match performance - van Raalte, J. L.; Brewer, B. W.; Rivera, P. M.; Petitpas, A. J. (Journal of Sport & Exercise Psychology, 1996)
The effect of self-talk on the performance of 24 junior tennis players (mean age 15.4 yr) during tournament matches was examined. It was found that negative self-talk was associated with losing and that players who reported believing in the utility of positive self-talk won more points than players who did not. The results suggest that the type of self-talk engaged in by athletes influences competitive outcomes. Implication: It is important for athletes to know why and how to engage in positive self-talk as part of their competition conduct.